Angle-resolved second-harmonic light scattering of colloidal interfaces - Peukert, Wolfgang; Braunschweig, Björn; Sauerbeck, Christian (Proceedings of a meeting held 3-8 November 2013, San Francisco, California, USA. Core Programming Area at the 2013 AIChE Annual Meeting: Global Challenges for Engineering a Sustainable Future, 2013)

Growth of gold nanoshells on colloidal silica characterized by in situ second-harmonic generation - Sauerbeck, Christian; Schürer, Benedikt; Haderlein, Michael; Braunschweig, Björn; Peukert, Wolfgang; Klupp Taylor, Robin (Engineering Sciences and Fundamentals 2013 - Core Programming Area at the 2013 AIChE Annual Meeting: Global Challenges for Engineering a Sustainable Future, 2013)
Metal nanoparticles and metal composite nanoparticles can have unique optical properties due to localized surface plasmon resonances and are therefore of particular interest in various applications. The resonance frequency of such particles is a function of their composition and their geometry. Gold nanoshells are comprised of a dielectric core and a thin gold shell. The optical properties of such particles can be readily tuned over a wide range by changing the ratio of the core diameter to the shell thickness. In order to impart better control over the optical properties of gold nanoshells a detailed understanding of the shell formation is of great importance. For that purpose it is necessary to monitor changes in surface composition and morphology in situ and in real time. However, most experimental methods lack the desired surface sensitivity or cannot be applied in situ under the required experimental conditions. For that reason we have applied second-harmonic generation (SHG) spectroscopy as a powerful surface sensitive technique which shows great potential to probe surfaces of nanoparticles under relevant experimental conditions1-3. In our contribution, we present results from synchronized SHG and UV/Vis/NIR spectroscopies that were obtained on-line during the seeded growth of gold shells on silica core particles. UV/Vis/NIR spectroscopy allows the monitoring of the coverage of gold and to estimate whether the shells are closed or not, while SHG shows a remarkable sensitivity to changes in the surface morphology which has not been accessible by other in situmethods so far. Notably, at intermediate conditions where a still incomplete shell exists on the core particle during shell growth, we observe first a steep increase in the second-harmonic intensity that is followed by a subsequent rapid decrease in SHG intensity. As the SHG signal is a function of the fundamental electric field to the fourth power, we propose that the observed maximum in the temporal evolution of the SHG intensity is caused by a local field enhancement due to crevices that are being formed in between individual gold islands. As shell growth proceeds, the surface coverage of these crevices decreases and closed shells are formed which results in a substantially decreased SHG signal. This hypothesis is corroborated by additional angle-resolved SHG experiments and ex-situ electron microscopy of gold shells with different gold coverages and surface morphologie
Keywords: nanoparticle; composite; plasmon; resonance; second-harmonic; core; shell

Molecular Mie model for second harmonic generation and sum frequency generation - Wunderlich, Sarina; Schürer, Benedikt; Sauerbeck, Christian; Peukert, Wolfgang; Peschel, Ulf (Physical Review B, 2011)
A theoretical model to simulate second harmonic and sum frequency generation from stratified spherical particles of arbitrary material is presented and compared with the widely used Rayleigh-Gans-Debye approximation and to experimental results from polystyrene particles with adsorbed malachite green molecules. In this model, the nonlinear polarization is caused by individual dipoles placed in the vicinity of the sphere and is simulated on a molecular basis. This offers greater flexibility to model more sophisticated systems.

Nonlinear spectroscopy meets particle interfaces: Revealing the interfacial structure of colloids - Sauerbeck, Christian; Schürer, Benedikt; Braunschweig, Björn; Peukert, Wolfgang (2012)

On the complex role of ammonia in the electroless deposition of curved silver patches on silica nanospheres - Sadafi, Fabrizio-Zagros; Sauerbeck, Christian; Braunschweig, Björn; Klupp Taylor, Robin (Crystengcomm, 2018)

Probing colloidal interfaces by angle-resolved second harmonic light scattering - Schürer, Benedikt; Wunderlich, Sarina; Sauerbeck, Christian; Peschel, Ulf; Peukert, Wolfgang (Physical Review B, 2010)
We report angle-resolved second harmonic light scattering from bare colloidal particles in water. A nonlinear Mie model is used to quantitatively analyze the nonresonant second harmonic (SH) scattering profiles and to determine the elements of the local second-order surface susceptibility. The SH signal is attributed to oriented and electrically polarized water molecules at the charged particle interface. The results show how angle-resolved SH light scattering can be applied to probe not only resonant excited dye molecules but also nonresonant molecules such as water at the interface of colloidal particles.

Second Harmonic Generation from metallic and dielectric spherical nanoparticles - Peukert, Wolfgang; Wunderlich, Sarina; Zhuromskyy, Oleksandr; Schürer, Benedikt; Haderlein, Michael; Sauerbeck, Christian; Peschel, Ulf (2012 Conference on Lasers and Electro-Optics (CLEO), 2012)
Due to symmetry-breaking at an interface, Second Harmonic Generation (SHG) is an extremely surface sensitive process. Therefore it is a widely used tool to study surfaces. Applied to colloidal nanoparticles it offers efficient means to monitor growth and molecular adsorption processes in real time and in situ. This makes SHG a preferred method to study the formation of core-shell plasmonic nanoparticles, which recently became quite popular because of their strong and tunable plasmonic resonances.
Keywords: Symmetry; spherical; nanoparticle; second; harmonic; generation; plasmon; Optical; surface; wave; Harmonic analysis; Plasmons; Frequency conversion; Dielectrics

Shedding light on the growth of gold nanoshells - Sauerbeck, Christian; Haderlein, Michael; Schürer, Benedikt; Braunschweig, Björn; Peukert, Wolfgang; Klupp Taylor, Robin (ACS nano, 2014)
Nanostructured particles containing noble metals can have highly tunable localized surface plasmon resonances and are therefore of particular interest for numerous applications. Nanoshells comprising a dielectric core and gold or silver shell are a widely researched systems because of the strong dependence of their optical properties on the ratio of core diameter to shell thickness. Although seeded-growth procedures have been developed to produce these particles, the many reported studies show significant variation in the nanoshell morphologies and hence optical properties. In order to establish processes that reproducibly synthesize nanoshells with high optical quality, it is necessary to develop techniques that monitor changes at the core particle surface during shell growth. For that purpose, we have carried out in situ nonlinear second-harmonic scattering (SHS) and linear vis-NIR extinction spectroscopy simultaneously during the seeded growth of gold nanoshells on silica core particles. Our SHS measurements show a striking variation in the nonlinear optical properties of the growing gold nanoshells. In comparison with linear optical measurements and with scanning electron microscopy (SEM) images made of gold nanoshells produced with varying shell completenesses, the SHS signal was observed to reach a peak intensity at a stage prior to shell closure. We attribute this high sensitivity of the SHS signal to the incomplete nanoshell surface morphology to the generation and subsequent degeneration of regions of electric field enhancement at gaps between isolated gold islands, which grow and coalesce. This conclusion is corroborated by finite-difference time-domain simulations of incomplete nanoshells. We suggest that the in situ analytical approach demonstrated here offers significant promise for future activities regarding the in-process optimization of the morphology and optical properties of metal nanoshells and other nanostructured plasmonic particles. © 2014 American Chemical Society.
Keywords: electric field enhancement; in situ vis-NIR spectroscopy; nanostructured particles; plasmonic particles; second-harmonic generation

Surface Charging and Interfacial Water Structure of Amphoteric Colloidal Particles - Peukert, Wolfgang; Braunschweig, Björn; Sauerbeck, Christian (Journal of Physical Chemistry C, 2014)
Colloidal stability and adsorption processes at particle surfaces are controlled by the generation of surface charge and the molecular structure of the resulting electrical double layers. We have applied second-harmonic light scattering (SHS) to address doublelayer charging and the orientation of water molecules at surfaces of amphoteric particles in unprecedented detail. For that purpose we have performed the first SHS experiments of neat polystyrene particles with a mixture of sulfate (R−O−SO3-) and amino (R-NH2) functional groups. Changing the pH has a dramatic effect on the surface potential which can be tuned from positive to negative values and has allowed us to record changes in SHS signal while the isoelectric point of the particles is being crossed. The SHS signal is a function of two contributions which are directly related to the first molecular layer, its orientation, and to a second electric field induced contribution of the unidirectional field within the interfacial electric double layer. Through additional charge screening experiments we measured the surface charge density for positively as well as for negatively charged particle surfaces and confirmed the isoelectric point, where an increase in ionic strength had little effect on the SHS intensity. Furthermore, we have determined the net orientation of water molecules directly adsorbed to the particle surface from pH-dependent changes in the relative phase of the two SHS contributions.
Keywords: colloid; adsorption; particle; surface; charge; electric; ionic; strength; double; layer